Taxonomy of European Damaeidae (Acari: Oribatida) III.Species of the Kunstidamaeus tenuipes (Michael, 1885) group, with a description of Kunstidamaeus fraterculus n. sp. from East Slovakia - Miko, Ladislav (Zootaxa, 2010)
Modern redescriptions and new diagnoses of three species of genus Kunstidamaeus, belonging to the “tenuipes” group— K. tenuipes (Michael, 1885), K. granulatus (Willmann, 1951), K. nivalis (Kulczynski, 1902) are given. Another species of this group, K. fraterculus n.sp., is described, based on individuals from Dreveník hill in East Slovakia. The group is characterized by relatively short, at least partly barbed, slightly club-shaped sensillus.